Evaluation of ovarian mass in reproductive age group: a 2 years prospective study in a tertiary care hospital in Haryana - Mahur, Beena; Kaur, Satwant; Gulia, Manish; Sehrawat, Sheetal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: In pre-eclampsia, there is increased uteroplacental resistance and reduced fetal perfusion due to inadequate invasion of spiral arterioles by trophoblast cells. This causes impaired fetal growth and fetal hypoxia. The objective was to assess the usefulness of fetal Doppler in predicting adverse perinatal outcome in preeclampsia. Methods: It was a prospective study conducted in Adesh medical college and hospital, Mohri, KKR, Haryana, India during the period of 2 years (2021-2022) on 92 women of reproductive age group from menarche to menopause, attending the hospital with complaints of lower abdomen pain, flatulence, lump in abdomen, changes in urinary and bowel habits and ovarian mass detected on clinical examination, or on ultrasound done for another reason. All details were filled in predesigned Performa. Results: There was a great deal of variation in the occurrence, behaviour, and clinical presentation of ovarian tumors. In addition to physical examination, laboratory investigations such as immunological testing and serum biomarkers and imaging procedures pelvic ultrasonography), can assist to determine the kind of pathology. The diagnosis of non-neoplastic and neoplastic ovarian lesions can be confused due to similar clinical presentations. Ovarian cancers have one of the worst prognoses of any cancer since there is insufficient screening to identify the disease early. Conclusions: It is imperative to raise awareness of this malignancy among Indian women. Because of the diversity of the Indian population, it is necessary to raise awareness of this issue across all linguistic and cultural divides. Not only should early detection be emphasized, but also “how to live well” with the illness should be discussed. All of these sophisticated, more recent diagnostic methods, along with the clinical and histo-morphological factors, can aid in early diagnosis, treatment planning, and prognostic importance.